Metalaxyl Effects on Antioxidant Defenses in Leaves and Roots of Solanum nigrum L. - de Sousa, Alexandra; AbdElgawad, Hamada; Asard, Han; Pinto, Ana; Soares, Cristiano; Branco-Neves, Simão; Braga, Teresa; Azenha, Manuel; Selim, Samy; Al Jaouni, Soad; Fidalgo, Fernanda; Teixeira, Jorge (Frontiers in Plant Science, 2017)
Overuse of pesticides has resulted in environmental problems, threating public health through accumulation in food chains. Phytoremediation is a powerful technique to clean up contaminated environments. However, it is necessary to unravel the metabolic mechanisms underlying phytoremediation in order to increase the efficiency of this process. Therefore, growth, physiological and biochemical responses in leaves and roots of Solanum nigrum L. exposed to the commonly used fungicide metalaxyl were investigated. This species shows characteristics that make it valuable as a potential tool for the remediation of organic pollutants. We found that once inside the plant, metalaxyl altered carbon metabolism, which resulted in a reduction of growth and lower biomass accumulation due to impairment of carbohydrate production (total soluble sugar, starch, rubisco) and increased photorespiration (glycolate oxidase, Gly/Ser ratio). A significant increase of antioxidant defenses (polyphenols, flavonoids, tocopherols, ascorbate, glutathione, superoxide dismutase, catalase, peroxidases, monodehydroascorbate- and dehydroascorbate reductase, gluthatione reductase) kept reactive oxygen species (ROS) levels under control (superoxide anion) leaving cell membranes undamaged. The results suggest that enhancing carbon assimilation and antioxidant capacity may be target parameters to improve this species’ phytoremediation capacities.